Implementasi Aplikasi Smart School Al-Wafa Sebagai Media Pendukung Pembelajaran Jarak Jauh (PJJ) Pada Mata Pelajaran PABP Selama Pandemi Covid-19 - Anggira Devia; Lalan Sahlani (Pendidikan Agama Islam STAIPI Persis Bandung, 2022)
Since the issuance of the Circular Letter of the Ministry of Education and Culture Number 4 of 2020 about Home Study Policy, the education system in Indonesia has undergone very drastic changes. Problems that arise during Studying at Home include: unpreparedness of students and teachers, unpreparedness existing systems in schools, and differences in devices and facilities owned by students. Educational institutions are required to be able to prepare an effective and efficient distance learning system for teachers and students then forces the community to be friendly with technology. The objectives of this research is: (1) to knowing learn planning through the Smart School Al-Wafa application, (2) to knowing the implementation of the Al-Wafa Smart School application, and (3) to knowing the supporting and inhibiting factors in implementing the Al-Wafa Smart School Al-Wafa application on PABP subjects at SMK Al-Wafa. This research was using a descriptive qualitative method with data collection techniques by observation, interview, and documentation of PABP teachers, headmaster, head of application developers, and 10 students. Based on the results of the study, it can be seen that PABP teachers at Al-Wafa Vocational School use the Al-Wafa Smart School application start from planning, learning, assessment, and evaluation during the Covid-19 pandemic conditions. Based on the data and the analysis, it can be concluded that (1) learn planning through Smart School Al-Wafa is the same as face-to-face learning but the process is digitized, (2) the implementation of Smart School Al-Wafa in the PABP subject has been able to accommodate learning activities well although it is necessary assisted by other companion applications, (3) the supporting factors are the network, devices, user capabilities, and the inhibiting factors are the practical material in the PABP subjects.